1995
DOI: 10.1002/1097-0142(19950501)75:9<2276::aid-cncr2820750914>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of combination therapy of radiation and local administration of OK-432 for esophageal cancer. Five-year survival and local control rate

Abstract: Background. Combination therapy consisting of radiation and local administration of OK‐432 was administered to 73 patients with esophageal cancer without distant metastases. Seventy patients were examined. The average age was 71 years. There were 60 males and 10 females. The mean tumor length was 7.0 cm. Methods. One mg of OK‐432 was administered endoscopically to and around the cancerous lesion at the beginning of radiotherapy and a second dose of 0.5 mg of OK‐432 was given in the same manner 2 weeks later. X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Various immunomodulators, such as streptococcal preparation OK-432, 15) 1→3-b-D-glucan, 16,17) heat-killed Lactobacillus casei preparation, 18) and alpha-galactosylceramide 19) have been reported to enhance the anti-tumor activities of radiotherapy in clinical or pre-clinical trials. These reports indicated that the combination of radiotherapy and immunotherapy could be useful for treating patients with cancer through augmentation of host defense mechanisms by immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Various immunomodulators, such as streptococcal preparation OK-432, 15) 1→3-b-D-glucan, 16,17) heat-killed Lactobacillus casei preparation, 18) and alpha-galactosylceramide 19) have been reported to enhance the anti-tumor activities of radiotherapy in clinical or pre-clinical trials. These reports indicated that the combination of radiotherapy and immunotherapy could be useful for treating patients with cancer through augmentation of host defense mechanisms by immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…OK‐432 has been widely used in Japan as adjuvant chemotherapy for lung cancer, 24 esophageal cancer, 25 gastrointestinal cancer, 26 bladder cancer 27 and intraperitoneal metastasis 28 . But few studies have reported OK‐432 as chemotherapy for hepatocellular carcinoma (HCC) and the precise immune mechanism of OK‐432 remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2A). It was difficult to insert the guide wire and delivery system, so OK‐432 was injected into the tumor endoscopically and radiotherapy was continued 6 . 7 Fourteen days after the injection of OK‐432, the diameter of the esophagus had increased to 3 mm ( Fig.…”
Section: Resultsmentioning
confidence: 99%